2016
DOI: 10.1159/000447587
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cardiovascular Risk Factors, Haematological and Biochemical Parameters, and Serum Endocan Levels in Patients with Lichen Planus

Abstract: Background and Objective: The current study aimed to evaluate cardiovascular risk factors, haematological and biochemical parameters, and serum endocan concentrations in lichen planus (LP) patients. Methods: This study was conducted with 86 cases, including 43 LP patients and 43 healthy controls. Cardiovascular risk factors, haematological and biochemical parameters, and endocan levels were evaluated. Results: The serum endocan concentrations of LP patients were not significantly different from those of the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
11
1
1
Order By: Relevance
“…On the other hand, there is another report describing that serum endocan levels in patients with psoriasis vulgaris are comparable with those in healthy controls . In addition, also in lichen planus, endocan levels are not increased in the sera . Thus, it is not still determined whether endocan is associated with development of inflammatory skin diseases.…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, there is another report describing that serum endocan levels in patients with psoriasis vulgaris are comparable with those in healthy controls . In addition, also in lichen planus, endocan levels are not increased in the sera . Thus, it is not still determined whether endocan is associated with development of inflammatory skin diseases.…”
Section: Introductionmentioning
confidence: 94%
“…with lichen planus when compared with the control group. 28 Belli et al 29 compared CBC parameters and MHR ratios in rosacea and control group. NLR ratio was found to be higher in rosacea patients when compared with the control group and they reported that MHR ratios were significantly higher in rosacea patients who also had metabolic syndrome and insulin resistance.…”
Section: Ta B L E 1 Distribution Of Patient and Control Groups By Gendermentioning
confidence: 99%
“…In a study, Kim et al [15] found higher PDW and MPV values in patients with psoriasis, a chronic inflammatory skin disease like DLE. In another study with lichen planus, Özlü et al [16] found higher PDW levels and lower MPV levels in the patient group when compared to a control group. Studies with SLE showed lower MPV values and higher PDW values in patients and a positive relationship between PDW and disease activity [17,18].…”
Section: Resultsmentioning
confidence: 90%